2021
DOI: 10.1002/nop2.927
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with endometrial carcinoma: A Longitudinal Study

Abstract: Aim To investigate the quality of life in patients with endometrial carcinoma and provide theoretical basis for nursing care. Design In this study, 69 patients diagnosed with endometrial carcinoma from 2016–2018 were included in the cohort. Methods Sixty‐nine patients from our hospital who underwent endometrial cancer surgeries were selected. The SF‐36 was used to investigate and analyse the patients’ quality of life in the first, second and third months after their operations. Questionnaires were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…As such, evaluations of QOL in other cancer populations have frequently used these generic health surveys with intriguing results. [13][14][15][16] In the current study, we explored the utility of self-reported mental and physical QOL metrics in predicting mortality among patients with RCC, regardless of stage, by using a national database augmented by the Medicare Health Outcomes Survey. We additionally performed an external test to confirm the utility of mental and physical QOL among patients with lower stage disease in a prospective registry of patients with small renal masses.…”
Section: Introductionmentioning
confidence: 99%
“…As such, evaluations of QOL in other cancer populations have frequently used these generic health surveys with intriguing results. [13][14][15][16] In the current study, we explored the utility of self-reported mental and physical QOL metrics in predicting mortality among patients with RCC, regardless of stage, by using a national database augmented by the Medicare Health Outcomes Survey. We additionally performed an external test to confirm the utility of mental and physical QOL among patients with lower stage disease in a prospective registry of patients with small renal masses.…”
Section: Introductionmentioning
confidence: 99%